A coniferyl aldehyde dehydrogenase gene from Pseudomonas sp. strain HR199 enhances the conversion of coniferyl aldehyde by Saccharomyces cerevisiae. (July 2016) - Adeboye, Peter Temitope; Olsson, Lisbeth; Bettiga, Maurizio
Highlights: Coniferyl aldehyde is inhibitory to S . cerevisiae . CALDH from Pseudomonas enhanced conversion of coniferyl aldehyde in B_CALD . ALD5 deletion limits the capacity of S . cerevisiae to convert coniferyl aldehyde. Abstract: The conversion of coniferyl aldehyde to cinnamic acids by Saccharomyces cerevisiae under aerobic growth conditions was previously observed. Bacteria such as Pseudomonas have been shown to harbor specialized enzymes for converting coniferyl aldehyde but no comparable enzymes have been identified in S . cerevisiae . CALDH from Pseudomonas was expressed in S . cerevisiae . An acetaldehyde dehydrogenase (Ald5) was also hypothesized to be actively involved in the conversion of coniferyl aldehyde under aerobic growth conditions in S . cerevisiae . In a second S . cerevisiae strain, the acetaldehyde dehydrogenase ( ALD5 ) was deleted. A prototrophic control strain was also engineered. The engineered S . cerevisiae strains were cultivated in the presence of 1.1 mM coniferyl aldehyde under aerobic condition in bioreactors. The results confirmed that expression of CALDH increased endogenous conversion of coniferyl aldehyde in S . cerevisiae and ALD5 is actively involved with the conversion of coniferyl aldehyde in S . cerevisiae .